User-Centred Design and Agile Development: Rebuilding the Swedish National Union Catalogue - Henrik Lindström; Martin Malmsten (Code4Lib Journal, 2008)
With a new generation of OPACs emerging that attempt to address longstanding shortcomings, how do we make sure that we do not lose ground again in the future? This article suggests a combination of iterative development and user-centred design as a way to develop systems that will meet the constantly changing expectations of users by providing both functionality and usability. It gives a short introduction to iterative software development and user-centred design. A case study of the development of the new version of LIBRIS (http://libris.kb.se), the Swedish National Union Catalogue, is used as an example of how these methodologies can benefit from each other in practice.